Indolent T-lymphoblastic proliferation with fibrolamellar hepatocellular carcinoma developed after colorectal adenocarcinoma: a case report - Wen Han; Bei Wang; Xiang Yong; Yi Zhang; Mingyu Shao; Chun Wang (Frontiers Media S.A., 2023)
Objective: Indolent T-lymphoblastic proliferation (iT-LBP) is a non-neoplastic disease with an indolent clinical course, manifesting as hyperplasia of immature extrathymic T-lymphoblastic cells. Isolated iT-LBP has been observed, but the majority of iT-LBP cases has been seen in conjunction with other diseases. iT-LBP is easily misdiagnosed as T-lymphoblastic lymphoma/leukemia, and understanding the disease of indolent T-lymphoblastic proliferation may prevent misdiagnosis and missed diagnosis in pathological diagnosis.Case presentation: We report a case morphology, immunophenotypic, and molecular features of iT-LBP combined with fibrolamellar hepatocellular carcinoma developed after colorectal adenocarcinoma and review relevant literature.Conclusion: iT-LBP combined with fibrolamellar hepatocellular carcinoma developed after colorectal adenocarcinoma is relatively rare and should always be considered as a differential diagnosis of T-lymphoblastic lymphoma and scirrhous hepatocellular carcinoma as the two disorders show highly similar clinical features.